New corpus-linguistic approaches to the investigation of poetic occasionalisms: The case of Johann Nepomuk Nestroy - Tumfart, Barbara; Dressler, Wolfgang U. (Yearbook of the Poznan Linguistic Meeting, 2017)
This paper reports on new approaches to the analysis of poetic occasionalisms, i.e. of words created by an author for a specific place in a literary text, and exemplifies them with the occasionalisms found in three comedies by Johann Nepomuk Nestroy, the greatest Austrian comedy writer and creator of new words in the 19th century. Corpus-linguistic search in Nestroy’s complete works and in large German electronic corpora enables better decisions with regard to whether an unfamiliar word was really an occasionalism. Comparison with Nestroy’s French models (never done so far) shows that these occasionalisms are really Nestroy’s original creations. Two new analyses of their relative audacity offer novel insights, which are corroborated by a first comparison between Nestroy’s and a rival’s occasionalisms. Next, the results of a cotextual and contextual analysis of occasionalisms are offered. Finally, for the first time it is studied to which actors the presentation of most occasionalisms was assigned in order to achieve optimal theatrical effects.